Penerapan Metode Demonstrasi untuk Meningkatkan Kemampuan Kognitif, Afektif, dan Psikomotor pada Pembelajaran IPA Pokok Bahasan Gaya - subhan uban hayun (Jurnal Ilmiah Wahana Pendidikan, 2020)
The objective to be achieved in this research is to study the application of Demonstration methods in Science Learning and cognitive, affective and psychomotor abilities in Science Learning about the Subject Style of Class IV students in Pilowo Elementary School. This type of research used in this study is the Class Research method we know as PTK (Classroom Action Research), this study consists of two cycles and an outline, containing four steps, namely (1) planning (planning), (2) implementing ( acting), (3) observation (observing), and (4) reflection. Based on data analysis and discussion, the conclusions that can be drawn from this study are student learning outcomes in science subject material style in cycle I on the cognitive aspects of students (40%), affective (35%), and psychomotor (45%) later completed in cycle II became Cognitive (85%), affective (90%), and psychomotor (85%) aspects, and 3 students who had not yet completed due to the limited research time not supported in cycle III and could only be remedied until they could achieve completeness. Thus the application of demonstration learning models can improve student learning in science subjects.